Det nye billede: 1 Kor 15,49 og forvandlingsmotivet i romersk visualitet - Pedersen, Thomas Lederballe (Dansk Teologisk Tidsskrift, 2019)
Discussing the scenario of future resurrection in 1 Cor. 15, Paul touches on the visual aspects of the bodily transformation which he claims will take place as a part of eschatological fulfilment. The con-cept of image plays a crucial role in this transformation as he believes the resurrected body will be shaped according to a “heavenly” exemplar, which he refers to as an image. Using examples drawn from Roman visual culture, both visual and textual, the article describes what type of image Paul’s Corinthian readers would have been inclined to think of in connection with a discussion of bodily transformation such as the one imagined by Paul.